2014
DOI: 10.1002/app.40636
|View full text |Cite
|
Sign up to set email alerts
|

Structure and mechanical properties of crosslinked glycidyl azide polymers via click chemistry as potential binder of solid propellant

Abstract: Depending upon the advantages of high efficiency, insensitivity to humidity and so on, the reaction of azide groups in glycidyl azide polymers (GAP) with alkynyl compounds has been used as a substitute of the urethane curing strategy to develop GAP‐based binder for solid propellant. In this work, an alkynyl compound of dimethyl 2,2‐di(prop‐2‐ynyl)malonate (DDPM) reacted with GAP to produce new crosslinked materials under the catalysis of Cu(I)Cl at ambient temperature, and showed great potential as a binder in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 24 publications
0
32
0
Order By: Relevance
“…The FGAP‐based polyurethane networks gave a tensile strength of 1.5 MPa and an elongation at break of 81.6%, which represent better mechanical properties compared to pure GAP‐based polyurethane networks (tensile strength of 0.66 MPa and elongation at break of 51.1%). This may be attributable to the flexibility of main chains of FGAP being improved via copolymerization resulting in a better intermolecular reaction and mechanical behaviors of polymeric binders . Therefore, it is suggested that the synthesis of a flexible structural FGAP in the binder formulation of solid propellants can be one of the most promising solutions for overcoming the poor mechanical properties of GAP‐based solid propellants.…”
Section: Resultsmentioning
confidence: 99%
“…The FGAP‐based polyurethane networks gave a tensile strength of 1.5 MPa and an elongation at break of 81.6%, which represent better mechanical properties compared to pure GAP‐based polyurethane networks (tensile strength of 0.66 MPa and elongation at break of 51.1%). This may be attributable to the flexibility of main chains of FGAP being improved via copolymerization resulting in a better intermolecular reaction and mechanical behaviors of polymeric binders . Therefore, it is suggested that the synthesis of a flexible structural FGAP in the binder formulation of solid propellants can be one of the most promising solutions for overcoming the poor mechanical properties of GAP‐based solid propellants.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the terminal hydroxyl group of glycidyl azide polymer (GAP) can be easily modified through various reactions such as esterification, acetalization, etherification, etc. [18][19][20][21][22][23][24]. In this paper, GAP was further functionalized via esterification with malonyl dichloride and subsequent brominate reaction to afford bromomalonic acid GAP ester (BM-GAP), which can easily react with C60 through a modified Bingel reaction [25] to afford a new fullerene derivative, namely, [60]fullerene GAP (C60-GAP), which perhaps could become a new material of energetic burning rate additive.…”
Section: Introductionmentioning
confidence: 99%
“…This decrease in breaking elongation is due to the higher cross-linked density. 42 As the weight ratio of the DDPM to Acyl-GAP increases from 5 % to 15 %, more and more alkynyl groups took part in triazole linkages and this increase of crosslinking points restricts the deformation, as a result of that tensile strength increased with an expense of breaking elongation. Figure 2 shows that optimum mechanical properties achieved by using 10 % of the DDPM and beyond this ratio although the tensile strength increases but the elongation decreases dramatically due to stiffer network associated to azido side linkage.…”
Section: Mechanical Propertiesmentioning
confidence: 99%